OSTEOARTHRITIS TREATMENT: MEDICAL INNOVATIONS AND NEW APPROACHES - Khamraev Botirjon (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: Osteoarthritis, also known as arthrosis, is a degenerative condition affecting the bones and joints, primarily linked to the wear and tear of joint tissues. While it is more commonly observed in older individuals, it can also occur in younger people. The main symptoms of osteoarthritis include pain, stiffness, limited range of motion, and muscle weakness around the affected joint. This article provides an in-depth overview of modern treatment methods for osteoarthritis, including medical advancements, therapeutic approaches, and the latest innovations aimed at improving joint function and quality of life for patients.